Clinical applications of single photon emission tomography in neuromedicine - Bartenstein, P.; Grünwald, F.; Kuwert, T.; Tatsch, K.; Sabri, O.; Benkert, O.; Fahlbusch, R.; Gründer, G.; Herholz, K.; Weiller, C. (Nuklearmedizin - NuclearMedicine, 2000)
This article gives in his second part a critical review of the clinical applications of SPECT with perfusion markers and receptor ligands in dementing disorders and psychosis. In addition this review discusses clinical applications of SPECT investigations with perfusion markers in inflammatory diseases of the central nervous system and in brain trauma.
Keywords: Single photon emission tomography (SPECT); dementia; schizophrenia; depression; brain trauma; inflammation